2021
DOI: 10.1590/1980-549720210019
|View full text |Cite
|
Sign up to set email alerts
|

Estado nutricional e risco metabólico em adultos: associação com a qualidade da dieta medida pela ESQUADA

Abstract: RESUMO: Objetivo: Analisar a associação entre qualidade da dieta medida pela Escala de Qualidade da Dieta (ESQUADA) e estado nutricional e risco metabólico em adultos. Métodos: Analisaram-se dados de 1.147 adultos (de 20 a 59 anos), participantes de inquérito populacional com amostragem complexa por conglomerado. Aferiram-se peso, altura, pregas cutâneas tricipital (PCT), subescapular (PSE) e circunferências da cintura (CC) e do braço (CB). Calcularam-se índice de massa corporal (IMC) e circunferência mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 32 publications
0
6
0
3
Order By: Relevance
“…and "excellent" 12 , expanding the possibilities data exploration, as can be seen in crosssectional studies already published. In these, ESQUADA was applied to investigate the associations between scores with metabolic risk and nutritional status 14 and food insecurity 28 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…and "excellent" 12 , expanding the possibilities data exploration, as can be seen in crosssectional studies already published. In these, ESQUADA was applied to investigate the associations between scores with metabolic risk and nutritional status 14 and food insecurity 28 .…”
Section: Discussionmentioning
confidence: 99%
“…Considering the pentagonal model of instrument validation 13 , previous studies have gathered evidence regarding the content, response process, internal structure, association with external measures, and consequences of using ESQUADA 12,14,15 . Knowledge of new evidence of ESQUADA's validity contributes to referencing the quality of the measure and can enhance its use in health surveys and monitoring dietary practices.…”
Section: Introductionmentioning
confidence: 99%
“…In the ESQUADA scale, poor or very poor diet quality are the levels with more frequent consumption of ultra-processed foods ( 11 , 33 ). Studies have shown that consuming foods with high energy density, such as ultra-processed and fast foods, is associated with weight change in undergraduates ( 34 , 35 ). In addition, increased consumption of ultra-processed foods and weight gain can increase the incidence of chronic noncommunicable diseases ( 36 ).…”
Section: Discussionmentioning
confidence: 99%
“…Quando analisado o consumo alimentar, os pacientes com DM apresentaram consumo mais elevado de alimentos cardioprotetores em relação aos alimentos de risco cardiovascular em relação aos que não tinham DM. Esse evento pode ser justificado pela causalidade reversa, onde os indivíduos tendem a modificar alguns comportamentos, após o diagnóstico de determinada doença, sendo essa característica comum em estudos transversais, que limita algumas associações, já que impossibilita a observação da temporalidade na relação entre a exposição e o desfecho do estudo 27 .…”
Section: Discussionunclassified